4
$\begingroup$

If we have to find the value of the following (1) $$ \sum_{r=1}^\infty\arctan \left(\frac{4}{r^2+3} \right) $$ I know that $$ \arctan \left(\frac{4}{r^2+3} \right)=\arctan \left(\frac{r+1}2 \right)-\arctan \left(\frac{r-1}2 \right) $$

I tried it lot and got a result but then stuck! (2)

(1) http://i.stack.imgur.com/26hA4.jpg (2) http://i.stack.imgur.com/g2vBb.jpg

$\endgroup$
  • $\begingroup$ Sorry due to low reputation , i cannot post image $\endgroup$ – user123733 Jul 25 '16 at 13:26
  • $\begingroup$ Are you Ok with my edit? Let me know. $\endgroup$ – Olivier Oloa Jul 25 '16 at 13:36
  • $\begingroup$ @OlivierOloa yes thank you $\endgroup$ – user123733 Jul 25 '16 at 13:37
6
$\begingroup$

$$ \begin{align} \sum_{r=1}^\infty\arctan\left(\frac4{r^2+3}\right) &=\sum_{r=1}^\infty\left[\arctan\left(\frac2{r-1}\right)-\arctan\left(\frac2{r+1}\right)\right]\\ &=\lim_{n\to\infty}\left[\sum_{r=1}^n\arctan\left(\frac2{r-1}\right)-\sum_{r=3}^{n+2}\arctan\left(\frac2{r-1}\right)\right]\\ &=\lim_{n\to\infty}\left[\frac\pi2+\arctan(2)-\arctan\left(\frac2n\right)-\arctan\left(\frac2{n+1}\right)\right]\\[6pt] &=\frac\pi2+\arctan(2) \end{align} $$

| cite | improve this answer | |
$\endgroup$
6
$\begingroup$

One may observe that summing $$ u_{r+1}-u_{r-1} $$ may be simplified as a telescoping sum:

$$ \sum_{r=1}^N\left(u_{r+1}-u_{r-1}\right)=\sum_{r=1}^N\left(u_{r+1}-u_{r}\right)+\sum_{r=1}^N\left(u_{r}-u_{r-1}\right)=u_{N+1}+u_N-u_1-u_0. $$

From the identity $$ \arctan \left(\frac{4}{r^2+3} \right)=\arctan \left(\frac{r+1}2 \right)-\arctan \left(\frac{r-1}2 \right) $$ by telescoping you then obtain $$ \begin{align} \sum_{r=1}^N\arctan \left(\frac{4}{r^2+3} \right)&=\arctan \left(\frac{N+1}2 \right)+\arctan \left(\frac{N}2 \right) \\\\&-\arctan \left(\frac12 \right)-\arctan \left(\frac{1-1}2 \right), \end{align} $$ giving, as $N \to \infty$ ,

$$ \sum_{r=1}^\infty\arctan \left(\frac{4}{r^2+3} \right)=2\arctan \left(\infty \right)-\arctan \left(\frac12 \right)=\frac{\pi}2+\arctan 2. $$

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ but how does other terms get cancelled $\endgroup$ – user123733 Jul 25 '16 at 13:40
  • $\begingroup$ @user123733 Like this $(u_2-u_0)+(u_3-u_1)+(u_4-u_2)+\cdot+(u_N-u_{N-1})$, do you see the terms cancel? $\endgroup$ – Olivier Oloa Jul 25 '16 at 13:42
  • $\begingroup$ @OlivierOloa are you sure? Shouldn't it be $\pi -\tan ^{-1}\left(\frac{1}{2}\right)$? $\endgroup$ – Pierpaolo Vivo Jul 25 '16 at 13:44
  • $\begingroup$ @OlivierOloa then one term will left $\endgroup$ – user123733 Jul 25 '16 at 13:44
  • 1
    $\begingroup$ Now this looks correct. (+1) $\endgroup$ – robjohn Jul 25 '16 at 14:13
3
$\begingroup$

$$\sum_{r=1}^N\arctan\left(\frac{r+1}2\right)-\sum_{r=1}^N\arctan\left(\frac{r-1}2\right)=\sum_{r=1}^N\arctan\left(\frac{r+1}2\right)-\sum_{r=-1}^{N-2}\arctan\left(\frac{r+1}2\right)$$ $$=\sum_{r=1}^N\arctan\left(\frac{r+1}2\right)-\sum_{r=1}^N\arctan\left(\frac{r+1}2\right)-\arctan\left(0\right)-\arctan\left(\frac{1}2\right)+\arctan\left(\frac{N}2\right)+\arctan\left(\frac{N+1}2\right)$$

Then let $N\rightarrow \infty$...

You then get $$\boxed {\pi -\arctan\left(\frac12\right)}$$

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ How r=-1 in your first step $\endgroup$ – user123733 Jul 25 '16 at 13:45
  • $\begingroup$ @user123733 set for example $u+1=r-1$ then $u=r-2$ then for $r=1$ you have $u=-1$ $\endgroup$ – GeorgSaliba Jul 25 '16 at 13:46
  • $\begingroup$ But everyone is getting another result $\endgroup$ – user123733 Jul 25 '16 at 13:54
  • $\begingroup$ @user123733 it is the same result... $\endgroup$ – GeorgSaliba Jul 25 '16 at 13:54
  • $\begingroup$ There it is pi/2 $\endgroup$ – user123733 Jul 25 '16 at 13:55
3
$\begingroup$

We already have plenty of slick answers through creative telescoping, so I will go for the overkill.
By crude estimations we have $\sum_{r\geq 3}\frac{4}{r^2+3}\leq\frac{\pi}{2}$, hence:

$$ \sum_{r\geq 3}\arctan\left(\frac{4}{r^2+3}\right) = \text{Arg}\prod_{r\geq 3}\frac{r^2+3+4i}{r^2}\tag{1}=\text{Arg}\prod_{r\geq 3}\left(1+\frac{(2+i)^2}{r^2}\right)$$ but due to the Weierstrass product for the $\sinh$ function: $$\prod_{r\geq 1}\left(1+\frac{(2+i)^2}{r^2}\right)=\frac{\sinh(2\pi+\pi i)}{\pi(2+i)}=-\frac{\sinh(2\pi)}{\pi(2+i)}\tag{2}$$ and that leads to: $$ \sum_{r\geq 1}\arctan\left(\frac{4}{r^2+3}\right) = \color{red}{\pi-\arctan\frac{1}{2}}.\tag{3}$$

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.